Analisis Penggunaan Gaya Bahasa Dalam Novel “Laut Bercerita” Karya Leila S. Chudori - Syakila Nur Haliza (LPPM Politeknik Pratama, 2023)
The novel is a popular literary work and much-loved by teenagers to adults. The novel also uses everyday language and also uses a beautiful style of language so that it makes its readers feel as if they are immersed in the story of the novel. Language style is the selection or use of figurative words that are arranged beautifully in a sentence that is useful for giving the impression of feelings and implied meanings. This study aims to determine the use of any language style contained in the novel entitled